TYPES OF ASSESSMENT AFFECTING IRANIAN EFL LEARNERS' GENERAL AND ACADEMIC SELF-EFFICACY - Abbas Ali Zarei; Zahra Usefli (Indonesian Journal of Learning and Instruction)
The purpose of this study is to compare the effects of three types of assessment (self, peer, and teacher) on EFL learners’ general and academic self-efficacy. The participants included a sample of 94 Iranian EFL learners studying English at IT English institute in Qazvin, Iran. A version of the Preliminary English Test (PET) along with the Persian translation of a 12-item general self-efficacy and an 8-item academic self-efficacy questionnaire were used to collect data. The participants were divided into three groups, and each group of participants was exposed to one of the treatment conditions. They were given the questionnaires both before and after the treatment. Two separate ANCOVA procedures were used to analyze data. No significant differences were found among the effects of the three types of assessment on general self-efficacy. However, both self-assessment and peer-assessment were found to be more effective on academic self-efficacy than teacher-assessment. Meanwhile, the difference between self and peer -assessment in academic self-efficacy was not statistically significant. Other than theoretical implications, the findings of this study may also have pedagogical implications for teachers, learners as well as syllabus designers.